2002
DOI: 10.1523/jneurosci.22-07-02780.2002
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson-Like Neurodegeneration Induced by Targeted Overexpression of α-Synuclein in the Nigrostriatal System

Abstract: Recombinant adeno-associated viral vectors display efficient tropism for transduction of the dopamine neurons of the substantia nigra. Taking advantage of this unique property of recombinant adeno-associated viral vectors, we expressed wild-type and A53T mutated human alpha-synuclein in the nigrostriatal dopamine neurons of adult rats for up to 6 months. Cellular and axonal pathology, including alpha-synuclein-positive cytoplasmic inclusions and swollen, dystrophic neurites similar to those seen in brains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
543
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 629 publications
(589 citation statements)
references
References 42 publications
(61 reference statements)
42
543
4
Order By: Relevance
“…Lentiviral vectors expressing human wild type or mutant forms of α-synuclein have been shown to lead to a progressive loss of nigral dopaminergic neurons by 24-35% in rats over 5 months 37 whereas adenoviruses expressing human α-synuclein have been shown to decrease nigral dopaminergic neurons by up to 80% in as short as 6 weeks, however these results are less consistent. 11,12,[38][39][40][41] In our model, miR-7T-AsRed significantly reduced TH expression by one-third at week 16 and two thirds at week 24. However, staining with VMAT2, another neuronal marker showed that there was only a 30% loss of neurons at 24 weeks suggesting that the nigral neurons had downregulated their activity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Lentiviral vectors expressing human wild type or mutant forms of α-synuclein have been shown to lead to a progressive loss of nigral dopaminergic neurons by 24-35% in rats over 5 months 37 whereas adenoviruses expressing human α-synuclein have been shown to decrease nigral dopaminergic neurons by up to 80% in as short as 6 weeks, however these results are less consistent. 11,12,[38][39][40][41] In our model, miR-7T-AsRed significantly reduced TH expression by one-third at week 16 and two thirds at week 24. However, staining with VMAT2, another neuronal marker showed that there was only a 30% loss of neurons at 24 weeks suggesting that the nigral neurons had downregulated their activity.…”
Section: Discussionmentioning
confidence: 55%
“…Downregulation of TH activity has previously been reported after overexpression of human α-synuclein as a protective mechanism of the cell. 38 Interestingly aggregated human α-synuclein has also been shown to reduce TH activity in dopaminergic neurons. 42 As miRs have many targets it is impossible to rule out that miR-7 may be affecting TH expression and dopaminergic neuronal health via another method other than upregulation of α-synuclein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viral vector gene transfer offers unique advantages for modeling, particularly for targeting brain regions and ages most associated with specific diseases. While α-synuclein (ASN) vector gene transfer models share features with PD such as loss of SN dopaminergic neurons in our previous study (Klein et al, 2002a) and two others (Kirik et al, 2002;Lo Bianco et al, 2002), motor dysfunction was not readily detected. To determine if the lack of behavioral effect was due to insufficient gene expression, we incorporated an enhancer element (Loeb et al, 1999) to boost ASN expression in this study.…”
mentioning
confidence: 84%
“…In vitro studies of a-synuclein aggregation provide possible hints as to the underlying situation : mixtures of human and mouse a-synuclein (as exist in the transgenic mouse brain) accumulate protofibrils, but fibrillize very slowly . Interestingly, virusmediated expression of rat a-synuclein in rat brain results in aggregation, but no neurodegeneration (Kirik et al 2002 ;Lo Bianco et al 2002). Further characterization of the aggregates formed by human and rat a-synuclein could provide important insights into the role of a-synuclein aggregation in the degeneration of dopaminergic neurons.…”
Section: In Vitro Fibril Formation Involves Transient Population Of Omentioning
confidence: 99%